Ti3+ self-doping in bulk of rutile TiO2 for enhanced photocatalysis. (15th March 2019) - Wang, Guojing; Zheng, Jun; Bi, Hong; Wang, Shuting; Wang, Jin; Sun, Jie; Guo, Yufeng; Wang, Chunchang
Abstract: A facile method, by sintering commercially available TiO2 in inert gas at high temperature, was used to obtain Ti 3+ self-doping blue rutile TiO2 ceramic powder. Our results indicate that Ti 3+ ions exist in bulk of TiO2 and the reduced TiO2 exhibits enhanced visible-light absorption. The reduced TiO2 possesses superior photocatalytic ability in photodegradation of methylene blue under Xe light illumination. Moreover, the reduced TiO2 exhibits good stability even after 12 months. This method provides an economical and universally applicable way to synthesize commercially available TiO2 powder with high and stable photocatalytic performance, which may have the promise for solar applications. Graphical abstract: The reduced TiO2 (Ti 3+ ions in bulk), by sintering commercially available TiO2 in inert gas at high temperature, possesses superior photocatalytic ability in photodegradation of methylene blue under Xe light illumination. Unlabelled Image